The Effect of Procedural Justice on Organizational Citizenship Behavior (OCB) with Trust as the Intervening Variable - Elok Ainur Latif; Mutia Pamikatsih (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
This study describes the effect of perceptions of procedural justice that employees feel on the organization and supervisor. Different sources that exist in perceptions of procedural justice will affect different OCB. This influence can be proven through the mechanism of social exchange relations that occur between organizational procedural justice and OCB which is mediated by trust. This research was conducted to determine the role of the target similarity model by examining the relationship of multifoci procedural justice, social exchange, and employee OCB together. The research sample involved nurses who worked at RSI (Islamic Hospital) Fatima Cilacap. Data collection was carried out using survey methods and questionnaires. Data analysis was performed using simple regression analysis through mediation. The results of this study found that the role of procedural justice in an organization is very important. Employees who have a perception of procedural justice will feel highly valued in their role as part of the organization so that the OCB shown to the organization tends to be high. The higher the level of perceptions of procedural justice felt by employees, the motivation of these employees to always show a higher OCB towards the organization and supervisor will also increase.